The relationship between alexithymia, anxiety, depression, and severity of the disease in psoriasis patients - Dizen Namdar, Nazlı; Arıkan, İnci (Journal of Surgery and Medicine, 2020)
Aim: It is known that psychological factors are significant in the onset and exacerbation periods of psoriasis. The purpose of this study is to evaluate the levels of anxiety, depression, and alexithymia in psoriasis patients and to determine their relationship with the severity of disease and quality of life. Methods: In this case-control study, 71 patients with psoriasis and 86 healthy people constituted the study and control groups, respectively. The clinical severity of psoriasis was determined by the “Psoriasis Area Severity Index” (PASI). “Dermatological Life Quality Index” (DLQI) form was conducted on the patients, and the “Toronto Alexithymia Scale”, “Beck Depression Scale” and “Beck Anxiety Scale” questionnaires were used for both the patients and the controls. Results: Anxiety and depression scores in psoriasis patients were significantly higher than controls (P=0.029, P=0.003, respectively), but there was no significant difference between alexithymia scores (P=0.158). A positive correlation was found between PASI and alexithymia scores (P=0.004), and between the DLQI score of psoriasis patients and anxiety, depression, alexithymia, and PASI scores (P<0.001, P=0.006, P=0.004, P=0.001, respectively). Conclusion: In our study, anxiety and depression levels were high in psoriasis. As the levels of anxiety, depression, and alexithymia increased, the quality of life deteriorated. Psoriasis patients should be not evaluated dermatologically only, but also be assessed psychologically and directed to the psychiatry outpatient clinic when necessary.